Validasi Pengembangan Modul Pembelajaran Ppkn Berbasis Mobile Untuk Meningkatkan Keterampilan Sosial Siswa Kelas XI SMA - Fella Farikhatus Sholikhah; Triana Rejekiningsih; Leo Agung Sutimin (Graduate School of Universitas Negeri Malang, 2022)
Abstract: The purpose of the research is to develop and validate the product in form a mobile-based module on Civics subjects. This study adopt the ADDIE model development design (Analysis, Design, Development, Implementation, and Evaluation). Validation and assessment from the validator, consist of: 1) validation from material experts obtained an average score of 3.72 qualified